The Application of Playing Therapy with Video Media on The Anxiety of Pre-School Age Children Due to Hospitalization in Regional Hospital dr. Soeratno Gemolong - Sulistyaningsih, Pita; Nurrohmah, Anjar; Purnamawati, Fitria (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: Hospitalization of preschool children is an emergency process, to be treated in a health facility. One of the impacts arising from hospitalization is in the form of anxiety, anxiety in children should not be underestimated, because it has the potential to hinder the child's health recovery process. It is especially important for managing anxiety in children undergoing hospitalization. Efforts that can be made on children's anxiety due to hospitalization can be overcome by playing therapy. Objective: The purpose of this study was the implementation of storytelling play therapy with video media on the level of anxiety due to hospitalization. Methods : Using a case study design, subjects to 2 preschool aged children (3-6 years) with inclusion and exclusion criteria, a measuring tool for anxiety using the SCAS anxiety scale (Spence Children's Anxiety Scale) to measure the respondent's anxiety level and the application of storytelling therapy with video media is given for approximately 10 minutes every day for 3 consecutive days. Results: Storytelling play therapy with video media in preschool-aged children (3-6 years) can reduce anxiety levels due to hospitalization. Conclusion: Storytelling therapy with video media has significant results in reducing anxiety in preschool-aged children who experience hospitalization.